Mesiodens-type supernumerary teeth evaluated through digital panoramic radiographs in a private radiology center in Manizales, Colombia - Pérez Gómez, Juan Sebastián (2024)
Objective: To evaluate mesiodens supernumerary teeth in digital panoramic radiographs taken between 2019 and 2020 at a private radiological center in Manizales, Colombia. Materials and Methods: A retrospective, descriptive, cross-sectional, observational study was conducted. The study population consisted of 1,000 panoramic radiographs from the radiological center in Manizales, Colombia, from 2019–2020. A virtual database was accessed for this purpose. The evaluated variables included age, sex, presence or absence of mesiodens, number of teeth with anomalies, tooth shape, position, location, and evolution. Statistical analysis was performed using frequencies and percentages. Results: The frequency of mesiodens supernumerary teeth was 3.8% (n=40), with a higher occurrence in males. Most cases involved a single mesiodens (n=38), with the highest number of cases in the age groups of 6 to 11 years (n=13) and 12 to 17 years (n=21), characterized by a rudimentary type and intraosseous evolution. Conclusion: Mesiodens type DS is a condition not very frequently found in the population studied; however, this study allowed us to carry out a characterization for Colombia, where there is not much scientific evidence in this regard, in order to have the possibility of contrasting it with other studies carried out nationally and internationally.